A review on adsorptive removal of oil pollutants (BTEX) from wastewater using carbon nanotubes - Anjum, H. (2019)
A progressive economic growth and proliferating global population caused adequate provision of clean water as a global issue. The systematic eradication of toxic pollutants from the environment has become a predominant matter from a biological and environmental perspective. Thus, adsorptive removal of hazardous components from wastewater is one of the most captivating strategies for purification technologies. Recently, carbon nanotubes (CNTs) have been reported to be very promising in the adsorption of various stable organic compounds due to their unique properties essential for further surface modification. In order to get the maximum removal of these pollutants, it is mandatory to understand the interaction mechanisms between the sorbent and sorbate. This review summarizes the recent literature on the adsorptive removal of BTEX from wastewater using CNTs. The impact of various factors (sorption sites of CNTs, physical properties of nanotubes, properties of background solution, and surface chemistry of CNTs) on the adsorption of BTEX over CNTs and the plausible interaction mechanisms such as hydrophobic interaction, electrostatic interaction, dispersive/repulsive interactions, Ï-Ï interactions and hydrogen bonding are critically reviewed. The present review has sorted out numerous prevailing gaps in the available information whilst recognizing a number of encouraging avenues and approaches for the upcoming research thrust. Â© 2018 Elsevier B.V.